Patient perception of orthodontic services during the Covid-19 pandemic: Persepsi pasien terhadap pelayanan ortodontis di masa pandemi Covid-19 - I Dewa Gde Budijana; Dwis Syahrul; Putu Leony Kartika Putri (Makassar Dental Journal PDGI Makassar, 2022)
In the field of dental and oral health services, orthodontists are one of the professions that have a high enough risk of being ex-posed to Covid-19. It is possible for each patient to transmit the SARS Cov-2 virus to orthodontists, other health workers and another patient. This study was aimed to determine patient perception to orthodontic clinic services and routine orthodontist vi-sits in orthodontic treatment during pandemic Covid-19. Methods: This study used adescriptive correlational, non-experimental study with a cross-sectional design. The sample of the study consisted of 134 orthodontic appliance users who had routine or-thodontic visits to orthodontic clinic around Denpasar City. Result. Based on the research, it is known that 132 orthodontic ap-pliance users (98,51% of the respondents) had a good perception of orthodontic clinic services during the Covid-19 pandemic and 117 orthodontic appliance users (87,31% of the respondents) had a fairly good perception of routine orthodontic treatment visits during the Covid-19 pandemic. In addition, the results of the Spearman’s rank correlation coefficient (Spearman’s ρ) test show a significance value of 0.065>0.05. It can be concluded that the orthodontic clinic services have had no impact on the routine orthodontic visits of orthodontic appliance users during pandemic Covid-19